2021
DOI: 10.7554/elife.62852
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage—how and why we age?

Abstract: Aging is a complex process that results in loss of the ability to reattain homeostasis following stress, leading, thereby, to increased risk of morbidity and mortality. Many factors contribute to aging, such as the time-dependent accumulation of macromolecular damage, including DNA damage. The integrity of the nuclear genome is essential for cellular, tissue, and organismal health. DNA damage is a constant threat because nucleic acids are chemically unstable under physiological conditions and vulnerable to att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
220
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(230 citation statements)
references
References 139 publications
8
220
1
1
Order By: Relevance
“…The maintenance of genomic stability is considered a major factor underlying human longevity with the accumulation of macromolecular damage, such as DNA damage, one of the most significant factors contributing to aging (49). We recover signatures of selection on DNA damage and repair related genes for both the robust and gracile capuchin branches independently, including enriched terms such as "double strand break repair", "cellular response to DNA damage stimulus", "DNA repair", and "DNA damage".…”
Section: Longevity Aging and Neurodegenerationmentioning
confidence: 99%
“…The maintenance of genomic stability is considered a major factor underlying human longevity with the accumulation of macromolecular damage, such as DNA damage, one of the most significant factors contributing to aging (49). We recover signatures of selection on DNA damage and repair related genes for both the robust and gracile capuchin branches independently, including enriched terms such as "double strand break repair", "cellular response to DNA damage stimulus", "DNA repair", and "DNA damage".…”
Section: Longevity Aging and Neurodegenerationmentioning
confidence: 99%
“…These cellular stressors lead to permanent activation of the DNA damage response (DDR) through ataxia telangiectasia mutated (ATM). The activated DDR results in the stabilization of tumor suppressor protein 53 (p53) and its transcriptional targets cyclin-dependent kinase inhibitor 1 (p21 CIP1 ) and cyclin-dependent kinase inhibitor 2A (p16 INK4a ), resulting in cell cycle arrest through inhibition of cyclin dependent kinases which prevent the phosphorylation of retinoblastoma (RB) and entrance into S phase of the cell cycle [ 25 , 26 , 27 , 28 ]. Senescent cells are characterized by increased cell size, senescent-associated beta-galactosidase (SA-β-gal) activity [ 29 ], upregulation of anti-apoptotic pathways [ 30 , 31 ], decreased lamin B1 [ 32 ], and a senescence-associated secretory phenotype (SASP) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that there is an association between age and DNA damage [ 12 ]. Specifically, several factors can contribute in increasing the levels of DNA damage, from both intrinsic and extrinsic sources [ 13 ]. Aging is considered as a progressive and biological phenomenon that leads to loss of physiological integrity and to an impairment of numerous functions, at the molecular, cellular, tissue and organ level [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, several factors can contribute in increasing the levels of DNA damage, from both intrinsic and extrinsic sources [ 13 ]. Aging is considered as a progressive and biological phenomenon that leads to loss of physiological integrity and to an impairment of numerous functions, at the molecular, cellular, tissue and organ level [ 12 , 13 ]. Several causes of aging have been hypothesized including an exacerbation of oxidative stress attributed to an imbalance between oxidant molecules and the antioxidant defence mechanisms [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation